Determinants of Attrition to Follow-Up in a Multicentre Cohort Study in Children-Results from the IDEFICS Study. (9th May 2013) - Hense, Sabrina; Pohlabeln, Hermann; Michels, Nathalie; Mårild, Staffan; Lissner, Lauren; Kovacs, Eva; Moreno, Luis A.; Hadjigeorgiou, Charalampos; Veidebaum, Toomas; Iacovello, Licia; Pitsiladis, Yannis; Reisch, Lucia; et al.
Abstract : Cohort participant retention is a crucial element and may depend on several factors. Based on data from a multicentre cohort of European children, the effect of baseline participation on attrition and the association with and the impact of single determinants in relation to the extent of attrition were investigated. Data was available for 16, 225 children from the IDEFICS baseline survey (2007/2008). Attrition was defined as nonparticipation in the first follow-up examination (2009/2010). Determinants of attrition were analysed by logistic regression. The statistical significance level was set at α = 0.01 to account for the large sample size. The strongest associations were seen for baseline item non-response, especially when information on migration background (odds ratio (OR) = 1.55; 99% confidence interval (CI): 1.04, 2.31), single parenthood (OR = 1.37; 99% CI: 1.12, 1.67), or well-being (OR = 1.46; 99% CI: 1.19, 1.79) was lacking. Drop-out proportion rose with the number of missing items. Overweight, low education, single parenthood and low well-being scores were independent determinants of attrition. Baseline participation, and the individual determinant effects seemed unrelated to the variation of the extent of attrition between study centres. A high level of item nonresponse as well as overweight and disadvantageous sociodemographic conditions were identified as main attrition determinants, suggesting the consideration of these aspects in conduct and analysis of cohort studies in childhood obesity research.